Infecção pelo vírus GB-C (GBV-C) em recém infectados pelo vírus da imunodeficiência humana tipo 1 (HIV-1): prevalência, incidência e modulação da ativação celular - Giret, Maria Teresa Maidana [UNIFESP] (2009)
GB virus C (GBV-C) is a single stranded positive sense RNA virus, which is a member of the Flaviviridae. It has a close sequence homology and genomic organization to hepatitis C virus (HCV). No disease has been associated with GBV-C infection but coinfection with human immunodeficiency virus (HIV) leads to improved morbidity and mortality for the HIV infected subjects. The mechanism of the beneficial effect of GBV-C appears to be mediated by alterations in the cellular immune response. In this study we investigated the frequency and genotyping characteristics as well as the impact of the GBV-C infection among recently HIV-1 infected individuals. In the first manuscript we examined the current knowledge concerning this co-infection and developed hypotheses to explain its effects. Subsequently, we described the rate of infection, the prevalence, incidence and genotypic GBV-C characteristics in this population. In that regard, a considerable frequency of GBV-C infection was observed and the phylogenetic analysis of the GBVC isolates revealed the predominance of genotypes 1 and 2. Also, it was observed an inverse correlation between GBV-C load and HIV-1 load at the enrollment and after one year of follow-up, and a positive, but not statistically significant, correlation between GBV-C load and CD4+ T lymphocyte counts. Finally, we have investigated the effect of GBV-C viremia on T cell activation in early HIV-1-infection. The volunteers were enrolled into two groups: GBV-C viremic and non viremic, all co-infected with HIV-1. They were evaluated for T cell counts, cellular activation markers, GBV-C RNA detection, and HIV-1 viral load. Non-parametric univariate and multivariate analyses were carried out to identify the variables associated with cellular activation. We demonstrated that the GBV-C viremia is correlated with a lower T cell activation in HIV-1-infected individuals and this effect was independent of HIV-1 viral load. The association between GBV-C replication and lower T-cell activation may explain, at least in part, the protection conferred by this virus against disease progression to immunodeficiency in HIV-1-infected patients.